1985
DOI: 10.7863/jum.1985.4.7.347
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of sonographic evaluation of ovarian size in patients with polycystic ovarian disease.

Abstract: The ovarian size of 44 patients with clinical and endocrinologic findings suggesting polycystic ovarian disease (PCOD) was studied by ultrasound examination. Reproducibility of the ovarian parameters (transverse, longitudinal, and anteroposterior diameters, and volume) was also evaluated. The endocrine status of each patient was evaluated by assay of blood levels of follicle-stimulating hormone (FSH), luteinizing hormone (LH), testosterone, 17 beta-estradiol (17 beta E2), and serum prolactin (PRL). Ovarian siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Studies based on transabdominal ultrasound have shown that normal ovaries were ellipsoid structures, with aver age volumes between 4.0 and 6.5 ml and the upper limit of ovarian volume between 5.7 and 7.6 ml [11,17,18], The ovarian volumes in patients with PCOS were twice those in normal ovaries, with average ovarian volume rangingfrom 12.0to 16.6 ml [8,10,11,14,[19][20][21], Pache et al [22], using transvaginal ultrasound, reported that the average ovarian volumes in normal women and patients with PCOS were 5.9 and 9.8 ml, respectively. In the present study, the ovarian volume (10.3 ml) observed in patients with PCOS was similarly about twice that (4.5 ml) in normal women and was in accordance with the results of Pache et al [22], Several investigators [10,11,23] have reported that 29-34% of ovaries in patients with PCOS were normal in size. Pache et al [22] also reported that a considerable overlap existed in ovarian volume between normal women and patients with PCOS.…”
Section: Discussionsupporting
confidence: 81%
“…Studies based on transabdominal ultrasound have shown that normal ovaries were ellipsoid structures, with aver age volumes between 4.0 and 6.5 ml and the upper limit of ovarian volume between 5.7 and 7.6 ml [11,17,18], The ovarian volumes in patients with PCOS were twice those in normal ovaries, with average ovarian volume rangingfrom 12.0to 16.6 ml [8,10,11,14,[19][20][21], Pache et al [22], using transvaginal ultrasound, reported that the average ovarian volumes in normal women and patients with PCOS were 5.9 and 9.8 ml, respectively. In the present study, the ovarian volume (10.3 ml) observed in patients with PCOS was similarly about twice that (4.5 ml) in normal women and was in accordance with the results of Pache et al [22], Several investigators [10,11,23] have reported that 29-34% of ovaries in patients with PCOS were normal in size. Pache et al [22] also reported that a considerable overlap existed in ovarian volume between normal women and patients with PCOS.…”
Section: Discussionsupporting
confidence: 81%
“…In 1981, Swanson et al [11] described PCO as enlarged and rounded, with a mean volume of 12 cm 3 and containing an increased number of small follicles (2-8 mm) encircling the ovarian cortex. However, the importance of ovarian size in diagnosis has lessened as various groups [12][13][14] have shown a considerable overlap between PCO and normal ovaries and as the upper limit of normal has decreased from greater than 10 cm 3 to 5.5 cm 3 [15]. This decrease may also reflect the broader inclusion criteria in the latter studies compared with Swanson et al who only included patients with enlarged ovaries and classic Stein-Leventhal syndrome at the extreme end of the clinical spectrum.…”
Section: Developments In Ultrasound Imagingmentioning
confidence: 99%
“…There are still indications to perform ultrasonography of the pelvis in women who present with these endocrine criteria for PCOS, i.e. to screen for anatomic abnormalities, such as polyps or endometrial hyperplasia causing dysfunctional uterine bleeding (64), or identify predictive factors for success or complications of ovulation induction (30,65). However, neither the morphology nor volume of the ovaries identify distinctive metabolic or reproductive abnormalities in women with hyperandrogenic chronic anovulation and routine ovarian ultrasonography in this group may be unnecessary.…”
Section: Discussionmentioning
confidence: 99%